2022
DOI: 10.3390/v14051006
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitors Enhance Efficacy of the Oncolytic Adenoviruses Ad∆∆ and Ad-3∆-A20T in Pancreatic and Triple-Negative Breast Cancer Models

Abstract: The prognosis for triple-negative breast cancer (TNBC) and pancreatic ductal adenocarcinoma (PDAC) is dismal. TNBC and PDAC are highly aggressive cancers with few treatment options and a potential for rapid resistance to standard-of-care chemotherapeutics. Oncolytic adenoviruses (OAds) represent a promising tumour-selective strategy that can overcome treatment resistance and eliminate cancer cells by lysis and host immune activation. We demonstrate that histone deacetylase inhibitors (HDACi) potently enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“… 23 , 24 , 25 HDAC inhibition assists multiple processes of oncolytic virotherapy, such as enhancing virus entry, replication, propagation, and spread; decreasing antivirus response; promoting apoptosis; and induction of tumor antigen expression. 27 , 28 Among several HDAC inhibitors, TSA, the pan‐HDAC inhibitor, targets class I (HDAC1, HDAC2, HDAC3, and HDAC8) and class II (HDAC4, HDAC5, HDAC6, HDAC7, HDAC9, and HDAC10) HDACs and is frequently combined with several OVs, such as adenovirus, 32 , 33 , 34 , 35 , 36 bovine herpesvirus type 1, 37 and herpes simplex virus. 38 , 39 , 40 It is also the most potent enhancer of VV replication and spread among other HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 , 25 HDAC inhibition assists multiple processes of oncolytic virotherapy, such as enhancing virus entry, replication, propagation, and spread; decreasing antivirus response; promoting apoptosis; and induction of tumor antigen expression. 27 , 28 Among several HDAC inhibitors, TSA, the pan‐HDAC inhibitor, targets class I (HDAC1, HDAC2, HDAC3, and HDAC8) and class II (HDAC4, HDAC5, HDAC6, HDAC7, HDAC9, and HDAC10) HDACs and is frequently combined with several OVs, such as adenovirus, 32 , 33 , 34 , 35 , 36 bovine herpesvirus type 1, 37 and herpes simplex virus. 38 , 39 , 40 It is also the most potent enhancer of VV replication and spread among other HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Since αvβ6-integrin is expressed only in solid tumours, including TNBC cell lines and tumours, and not in healthy tissues (Whilding et al, 2017), we suggest that Ad5-3Δ-A20T has potential for translation into the clinic for treatment of TNBC. We recently demonstrated that the replication and anti-tumour efficacy of OAds including Ad5-3Δ-A20T can be augmented when combined with novel therapeutics such as histone deacetylase inhibitors (HDACis) (Rodríguez et al, 2022).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Furthermore, a recombinant ADV expressing granulocyte-macrophage colony-stimulating factor (GMCSF) in combination with immune checkpoint inhibitors (ICIs) was able to control tumor growth in vivo and promote increased survival compared to control-treated animals [ 121 ]. Pairing histone deacetylase inhibitors (HDACis) with a recombinant ADV expressing an αvβ6-integrin-binding peptide from foot and mouth disease virus demonstrated effective tumor reduction and increased viral replication in a SUM159 xenograft mouse model [ 122 ].…”
Section: Preclinical Ovs For Tnbcmentioning
confidence: 99%